Pengaruh Perencanaan Pajak dan Profitabilitas Terhadap Manajemen Laba Pada Perusahaan Manafaktur Subsektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia - Cecep Nur Pratama; Hisnol Djamali; Annas Lalo (Journal of Management and Social Sciences, 2022)
This study aims to determine the effect of tax planning and profitability on earnings management in the food and beverage subsector manufacturing companies listed on the Indonesia stock exchange.en. The population in this study are manufacturing companies in the food and beverage sector which are listed on the Indonesia Stock Exchange during 2019-2021, where there are 30 companies, while the sample taken is 22 companies with a sampling technique using purposive sampling. The data processed were 66 samples that had been tested for classical assumptions in the form of assumptions of normality, multicollinearity, heteroscedasticity and autocorrelation. Methods of data analysis using multiple regression techniques. The results showed that Tax Planning had a positive and significant effect on Earnings Management, Profitability had a positive and significant effect on Earnings Management.